Evaluation of Visceral Adipokines: Omentin, Vaspin, and Visfatin in Patients with Gestational Diabetes Mellitus - Mehmet Yilmaz; Serif Aksin; Nizamettin Bozbay; Deniz Balsak; Yasmin Aboalhasan; Fatma Zehra Kurnuç; Leyla Seyhan; Ibrahim Batmaz (IMR Press, 2024)
Background: Gestational diabetes mellitus (GDM) is a common metabolic disorder characterized by glucose intolerance that develops during pregnancy. The underlying pathophysiological mechanisms of GDM involve complex interactions between genetic, environmental, and hormonal factors, including adipokines secreted by visceral adipose tissue. Omentin, vaspin, and visfatin are adipokines believed to influence insulin sensitivity and inflammation, though their precise relationship with GDM remains unclear. This study aimed to examine the association between these adipokines and GDM. Methods: This single-center, prospective controlled cohort study included 87 pregnant patients diagnosed with GDM via an oral glucose tolerance test (OGTT) between the 24th and 28th weeks of gestation, along with 87 control subjects without GDM. Serum levels of omentin, vaspin, and visfatin were measured using enzyme-linked immunosorbent assay (ELISA), and their association with GDM was analyzed. Results: Our results demonstrated that omentin levels were significantly higher in the GDM group compared to the control group (p = 0.012), while no significant differences were observed in vaspin and visfatin levels (p > 0.05). An omentin cut-off value of 29.0 ng/mL predicted GDM with 59.1% sensitivity and 59.1% specificity, suggesting its potential as a biomarker for GDM. Conclusions: This study underscores the unique role of omentin in GDM, in contrast to the non-significant changes observed in vaspin and visfatin levels. The elevated omentin levels in GDM patients suggest its potential as a biomarker for diagnosing and managing GDM. Further research is needed to elucidate the mechanisms through which omentin contributes to the pathophysiology of GDM. Clinical Trial Registration: NCT05463237, https://clinicaltrials.gov/study/NCT05463237.